Effect of Substrate Temperature and Target-Substrate Distance on Growth of TiO2 Thin Films by Using DC- Reactive Sputtering Technique - Laith Rabih; Sudjatmoko -; Kuwat Triyana; Pekik Nurwantoro (Department of Physics Universitas Gadjah Mada, 2014)
Titanium oxide (TiO2) thin films have been deposited by a DC sputtering technique onto microscope glass slides. The effect of substrate temperature (Ts) and target-substrate distance (Dts) on some optical and electrical properties have been studied each individually. The structure of TiO2 thin films has been improved and became more crystalline when Ts has been increased (from 150 ºC to 250 ºC). The conductivity (ϭ), deposition rate (DR) and average values of grain size (G.S) have been increased with increasing Ts while the values of band gap (Eg) and weight percentage of the anatase phase (WA) have been decreased. The thickness of TiO2 film has been increased from 920 nm to 960 nm with increase Ts while it has been decreased from 960 nm to 680 nm with increase Dts (from 25mm to 35mm). As Dts has been increased, the conductivity ϭ, thickness (d) and average values of grain size have been decreased. The decreasing of conductivity at Dts=35 maybe attributes to increase the weight percentage of the rutile phase (WR). The XRD results show that the TiO2 structure phase has been varied. The results show that the optical and electrical properties of TiO2 film affected by changes the condition parameters especially Ts and Dts as well as the density and energy of the impinging atoms. The surface morphology and component of TiO2 thin films, resistance, optical transmittance and structure of film were characterized by SEM (EDX), I-V meter, UV-VIS spectrophotometer and XRD respectively.